Assessment of the Characteristics of Waxy Rice Mutants Generated by CRISPR/Cas9 - Fu, Yuhao; Luo, Tingting; Hua, Yonghuan; Yan, Xuehai; Liu, Xu; Liu, Ying; Liu, Yiping; Zhang, Baoli; Liu, Rui; Zhu, Zizhong; Zhu, Jun (Frontiers in Plant Science, 2022)
The cooking and eating quality of rice grains is a major focus from a consumer’s perspective and is mainly determined by the apparent amylose content (AAC) of the starch. Waxy rice, a type of rice with an AAC of less than 2%, is an important goal for the breeding of high-quality rice. In recent years, the cloning of the Waxy (Wx) gene has revealed the molecular mechanism of the formation of waxy traits in rice. However, there have been limited studies on the physicochemical properties, such as gelatinization temperature, rapid viscosity analyzer profile and amylopectin fine structure of wx mutants. In the current study, a rapid and highly efficient strategy was developed through the CRISPR/Cas9 gene-editing system for generating wx mutants in the backgrounds of five different rice varieties. The wx mutation significantly reduced the AAC and starch viscosity but did not affect the major agronomic traits (such as plant height, panicle number per plant, grain number per panicle, and seed-setting frequency). Incorporation of the wx mutation into varieties with low initial AAC levels resulted in further reduction in AAC, but without significantly affecting the original, desirable gelatinization traits and amylopectin structural types, suggesting that parents with low initial AAC should be preferred in breeding programs.